2022
DOI: 10.1002/ps.7303
|View full text |Cite|
|
Sign up to set email alerts
|

Developing the radiation‐based sterile insect technique (SIT) for controlling Aedes aegypti: identification of a sterilizing dose

Abstract: Background: The sterile insect technique (SIT) is emerging as a tool to supplement traditional pesticide-based control of Aedes aegypti, a prominent mosquito vector of microbes that has increased the global burden of human morbidity and mortality over the past 50 years. SIT relies on rearing, sterilizing and releasing large numbers of male mosquitoes that will mate with fertile wild females, thus reducing production of offspring from the target population. In this study, we investigated the effects of ionizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
(165 reference statements)
0
11
1
Order By: Relevance
“…aegypti and Ae. albopictus that are irradiated at doses which induce sterility in males of the same species are more likely to blood‐feed, a clear contrast to our observations in Chen et al 2 . There are at least two reasons why the results of these two studies differ.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…aegypti and Ae. albopictus that are irradiated at doses which induce sterility in males of the same species are more likely to blood‐feed, a clear contrast to our observations in Chen et al 2 . There are at least two reasons why the results of these two studies differ.…”
contrasting
confidence: 99%
“…Considering the contrasting findings between the investigation conducted by Moretti et al 1 . and Chen et al 2 . we regret not finding their paper in our literature search before submission of our article.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…It has been shown that X-rays provide a practical and effective alternative to gamma-ray for sterilization of insects, are often less expensive, and are subjected to less stringent regulations [20][21][22] . Ionizing radiation induces dominant lethal mutations in the chromosomes of germ cells of the insect 19 that significantly affect the fertility of males [22][23][24][25] . The more the absorbed dose increases, the higher the sterility, and the higher the risk of off-target, somatic damage occurring, which can negatively impact insect quality 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The method requires the production of large numbers of sterilized males, which are released into the environment, and mate with a local population of mosquitoes. If the ratio of sterilized males to females is high enough, they will outcompete the non-sterile males and lead to a reduction in the mosquito population [ 33 , 34 , 35 , 36 ]. The production of sterilized males is challenging and makes it difficult to translate into largescale mosquito control programs.…”
Section: Introductionmentioning
confidence: 99%